2015
DOI: 10.1002/nop2.31
|View full text |Cite|
|
Sign up to set email alerts
|

Developing an instrument to self‐evaluate the Discharge Planning of Ward Nurses

Abstract: AimsTo develop the Discharge Planning of Ward Nurses (DPWN), a Japanese self‐evaluation instrument for ward nurses' discharge planning practices.DesignCross‐sectional survey.MethodsParticipants were 624 ward nurses from six hospitals in Japan with a discharge planning department. Items about discharge planning practices were collected from literature and interviews with nurses and researchers. Construct validity, concurrent validity, internal consistency and test–retest reliability were tested.ResultsInitially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In this study, we used the Discharge Planning Scale for Ward Nurses (DPWN) (Sakai, Mitani, Takai, Fukahori & Ogata, 2015), an international scale that covers the perspectives of continuous care and the contents of discharge support activities in collaboration with multidisciplinary professionals, to examine the implementation of effective discharge planning for alcoholics. This scale was developed in Japan and is considered to be appropriate for the Japanese situation.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used the Discharge Planning Scale for Ward Nurses (DPWN) (Sakai, Mitani, Takai, Fukahori & Ogata, 2015), an international scale that covers the perspectives of continuous care and the contents of discharge support activities in collaboration with multidisciplinary professionals, to examine the implementation of effective discharge planning for alcoholics. This scale was developed in Japan and is considered to be appropriate for the Japanese situation.…”
Section: Methodsmentioning
confidence: 99%
“…Discharge planning practice for end-stage cancer patients was assessed using the self-reported Discharge Planning of Ward Nurses (DPWN) scale developed by Sakai et al [ 14 ]. The scale was developed to measure general discharge planning practice in nurses who do not specialize in working with patients with end-stage cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding skills, it was found that communication skills were important and had an impact on discharge planning practice [ 13 ]. General ward nurses’ discharge planning practice consists of understanding the intentions and wishes of patients and their families, providing information to them, supporting decision making, and cooperating with other healthcare providers [ 14 , 15 ]. To fulfill these roles, communication skills are indispensable.…”
Section: Introductionmentioning
confidence: 99%
“…To improve discharge planning practice, scales have been developed for nurses to self‐evaluate discharge support (home transfer support), which have helped nurses effectively. The currently used validated self‐evaluation scales for discharge planning in Japan are the Discharge Planning of Ward Nurses (DPWN) scale (Sakai et al, 2016), the Discharge Planning‐Process Evaluation Measurement (Chiba, 2005), and the Nurses' Discharge Planning Ability Scale (Tomura et al, 2013). These self‐evaluation scales are valuable instruments.…”
Section: Introductionmentioning
confidence: 99%